2012
DOI: 10.1021/ct300091w
|View full text |Cite
|
Sign up to set email alerts
|

The Solvation Structure of Na+ and K+ in Liquid Water Determined from High Level ab Initio Molecular Dynamics Simulations

Abstract: Knowledge of the hydration structure of Na(+) and K(+) in the liquid phase has wide ranging implications in the field of biological chemistry. Despite numerous experimental and computational studies, even basic features such as the coordination number of these alkali ions in liquid water, thought to play a critical role in selectivity, continue to be the subject of intensive debates. Simulations based on accurate potential energy surfaces offer one approach to resolve these issues by providing reliable results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
249
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(277 citation statements)
references
References 57 publications
(103 reference statements)
27
249
1
Order By: Relevance
“…7 and 8 as well as Table I. For the QM/MM simulations, they are in line with those of previous experimental 269,270 and theoretical 155,219 studies reported in the literature (see also other references in Table I). …”
Section: B Hydration Structure and Dynamicssupporting
confidence: 90%
See 3 more Smart Citations
“…7 and 8 as well as Table I. For the QM/MM simulations, they are in line with those of previous experimental 269,270 and theoretical 155,219 studies reported in the literature (see also other references in Table I). …”
Section: B Hydration Structure and Dynamicssupporting
confidence: 90%
“…The QM/MM MD simulations rely on the quantum-mechanical charge field (QMCF) approach, 158,159 which belongs to the family of adaptive QM/MM methods 148,149,160 and has been applied with success in the past to investigations of solvated ions, 153,154 molecules, 161,162 coordination complexes, 163,164 and biomolecular systems. 165,166 Single-determinantal approaches such as ab initio HartreeFock 167,168 (HF) or DFT 169,170 have a limited accuracy/reliability 120,[123][124][125][126][127]155,[171][172][173][174][175][176] in the description of hydration phenomena. Thus, a correlated ab initio method is employed here to describe the QM subsystem (ion and first hydration shell), namely, resolution-of-identity secondorder Møller-Plesset perturbation 177,178 (RIMP2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ab initio molecular dynamics of ions in solutions can be performed, and many such studies have been reported (e.g., [48][49][50][51][52] ). Unfortunately, such simulations are limited to small systems and short periods.…”
Section: Approachmentioning
confidence: 99%